2012
DOI: 10.1038/ncomms2261
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adult neurogenesis impairs population coding of similar contexts in hippocampal CA3 region

Abstract: Different places may share common features, but are coded by distinct populations of CA3 neurons in the hippocampus. Here we show that chemical or genetic suppression of adult neurogenesis in the hippocampus impairs this population-based coding of similar (but not dissimilar) contexts. These data provide a neural basis for impaired spatial discrimination following ablation of adult neurogenesis, and support the proposal that adult neurogenesis regulates the efficiency of a pattern separation process in the hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 25 publications
8
132
1
Order By: Relevance
“…In this study, researchers identified new neurons and observed neurogenesis occurring in the hippocampal region, a brain region that controls certain types of memory [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, researchers identified new neurons and observed neurogenesis occurring in the hippocampal region, a brain region that controls certain types of memory [16].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent IEG studies cast light on CA3 activity in mice with reduced or ablated neurogenesis. Niibori et al (2012), using combined arc immunohistochemistry (remote experience) and in situ hybridization (recent experience), found greater overlap in the CA3 pyramidal neurons activated by two similar environments (but not markedly different ones) when neurogenesis was reduced, i.e., less distinct representations were formed, indicative of reduced pattern separation. Denny et al (2012) found that in neurogenesis-ablated mice that displayed poor contextual memory retrieval following brief encoding sessions (see "Contextual and spatial memory"), this was correlated with reduced reactivation of CA3 pyramidal neurons when mice were reexposed to the shock-associated context.…”
Section: )?mentioning
confidence: 99%
“…Increased excitability, together with the enhanced plasticity, would make new neurons more suitable for signal amplification rather than sparsification. At the cellular level, a recent study has shown that a modest reduction of immature adult-born neurons altered the activation of CA3 neurons when coding similar, but not dissimilar (or novel) contexts (Niibori et al 2012). At the behavioral level, the data obtained so far suggest that immature neurons are not involved in this process (Deng et al 2013).…”
Section: Neurogenesis and Hippocampal Memory Systemmentioning
confidence: 99%